Enhanced hop-by-hop routing algorithms for underwater acoustic sensor networks - Tariq, Moeen Ud Din (2017)
Underwater Acoustic Sensor Network (UW-ASN) is a wireless network infrastructure applicable in deep ocean to sense, collect and transmit information to seashore data collector. Underwater sensor network consists of sensor nodes disposed in different depths, equipped with a low bandwidth acoustic modem and acts collaboratively to route the packet from one node to another. Underwater routing protocols provide route information to underwater sensor nodes to transmit collected information efficiently using an optimal path. Routing protocol related to UW-ASN is identified with the issues of low energy consumption, high end-to-end delay and shorter network lifetime. These are due to the distribution of unnecessary information packet flooding in route establishment, improper selection of next hop neighbour and inefficient routing path generation. This research develops a routing protocol that will be able to control flooding of hello packet at information distribution phase, to calculate link quality and composite metric cost for next hop selection and to regularly update the energy status in order to achieve optimum balance in routing path. The developed protocol is called Distance based Reliable and Energy Efficient (DREE) consists of three schemes. The first scheme is called distance calculation and information distribution scheme that calculates the distance between potential neighbours and distribute the local information in an energy efficient manner. The second scheme is route planning and data forwarding scheme in which a node calculates the link quality towards its neighbours and selects a path based on physical distance, link quality and node energy information. Finally, the third scheme is energy balancing scheme that provides each node with new energy status of its neighbours on regular basis. DREE is compared with a Reliable and Energy Efficient routing protocol (R-ERP2R) and Depth based Routing (DBR) protocol. Simulation shows that DREE reducing energy consumption in the information distribution phase by 187% and 179% compared to R-ERP2R in random and grid topology respectively. DREE achieves higher packet delivery ratio of 96% with a similar end-to-end delay as R-ERP2R. DREE improves packet delivery ratio by 7% and 13% over R-ERP2R and DBR, with 9.3% and 201% less energy consumption respectively in data forwarding phase. Finally, DREE improves network lifetime by 18% and 74.5% compared to R-ERP2R and DBR protocols.